Effect of Magnetic Field on Unsteady Free Convection Flow Over a Vertical Wavy Surface (Dhaka University Journal of Science, 2017)
Unsteady free convection flow over a vertical wavy surface in the presence of magnetic field is presented. The governing equations are reduced to a system of dimensionless equations by using appropriate transforms. Resulting equations are then solved numerically employing implicit finite difference method. Effects of the amplitude-wavelength ratio and the magnetic field parameter are discussed in terms of the local skin-friction coefficient, the local Nusselt number and the local Sherwood number.Dhaka Univ. J. Sci. 65(2): 85-90, 2017 (July)